2019
DOI: 10.1371/journal.pone.0211916
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin: Anti-tumor activity in a pre-clinical colorectal cancer model

Abstract: Objectives Salinomycin is a polyether antibiotic with selective activity against human cancer stem cells. The impact of salinomycin on patient-derived primary human colorectal cancer cells has not been investigated so far. Thus, here we aimed to investigate the activity of salinomycin against tumor initiating cells isolated from patients with colorectal cancer. Methods Primary tumor-initiating cells (TIC) isolated from human patients with colorectal liver metastases or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 59 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…Consistently, in vivo studies proved that salinomycin may reduce metastasis formation in mammary tumor mouse model, bladder tumor rat model and intravenous mouse tumor model (Gupta et al, 2009;Kopp et al, 2014;Qu et al, 2015). Importantly, salinomycin is able to suppress the late stages of autophagy contributing to the ROS generation and mitochondria dysfunction (Klose et al, 2019). This might explain the mechanism by which salinomycin targets mitochondrial K + /H + exchange and prevents migration, invasion and metastasis.…”
Section: Therapeutic Targeting Metastasismentioning
confidence: 60%
See 1 more Smart Citation
“…Consistently, in vivo studies proved that salinomycin may reduce metastasis formation in mammary tumor mouse model, bladder tumor rat model and intravenous mouse tumor model (Gupta et al, 2009;Kopp et al, 2014;Qu et al, 2015). Importantly, salinomycin is able to suppress the late stages of autophagy contributing to the ROS generation and mitochondria dysfunction (Klose et al, 2019). This might explain the mechanism by which salinomycin targets mitochondrial K + /H + exchange and prevents migration, invasion and metastasis.…”
Section: Therapeutic Targeting Metastasismentioning
confidence: 60%
“…Salinomycin is an antibiotic from the polyether ionophores group widely used in agriculture (Managò et al, 2015). Recently, it has been revealed that it possesses anticancer properties in different types of cancer (Klose et al, 2019;Tang et al, 2011). Salinomycin may target chemoresistant tumor cells, inhibiting Wnt/β-catenin and Sonic Hedgehog signaling pathways (Managò et al, 2015).…”
Section: Therapeutic Targeting Metastasismentioning
confidence: 99%
“…Salinomycin was intravenously administered every second day for 3 weeks, resulting in inhibition of disease progress for months without any serious long‐term side effects (Naujokat & Steinhart, ). Salinomycin at 4 mg·kg −1 ·day −1 showed effective antitumour activity in a patient‐derived mouse xenograft model of colorectal cancer (Klose et al, ). Moreover, intraperitoneal injection of salinomycin at doses of 3 and 5 mg·kg −1 ·day −1 markedly suppressed tumour growth in human gastric cancer xenografts without causing obvious toxicities (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Salinomycin at 4 mg·kg −1 ·day −1 showed effective antitumour activity in a patient-derived mouse xenograft model of colorectal cancer (Klose et al, 2019). Moreover, intraperitoneal injection of salinomycin at doses of 3 and 5 mg·kg −1 ·day −1 markedly suppressed tumour growth in human gastric cancer xenografts without causing obvious toxicities .…”
Section: Salinomycin Attenuates Colorectal Tumour Growth By Blockinmentioning
confidence: 96%
“…As an example, salinomycin (procoxacin), a polyether potassium ionophore antibiotic, targets breast and nasopharyngeal CSCs through suppression of the Wnt/β-catenin pathway [ 34 , 63 , 64 ] ( Figure 1 ). The anticancer effect of salinomycin was observed when it was used alone or combined with other drugs (5-fluorouracil and oxaliplatin) [ 65 ] ( Figure 1 ). Epigallocatechin-3-gallate (EGCG), which blocks the Wnt/β-catenin signaling pathway, showed anticancer effect against colorectal CSCs [ 66 , 67 ] ( Figure 1 ).…”
Section: Mitochondrial Respiration and Oxidative Phosphorylation In Cscsmentioning
confidence: 99%